In Vivo 3D MRI Measurement of Tumour Volume in an Orthotopic Mouse Model of Prostate Cancer. (25th April 2019) - Ni, Jie; Bongers, Andre; Chamoli, Uphar; Bucci, Joseph; Graham, Peter; Li, Yong
Prostate cancer (CaP) is the most commonly diagnosed cancer in males in western countries. Orthotopic implantation is considered as an ideal xenograft model for CaP study, and noninvasive measurement of tumor volume changes is important for monitoring responses to anticancer therapies. In this study, the T2-weighted fast spin echo sequence magnetic resonance imaging (MRI) was performed on a CaP orthotopic non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mouse model weekly for 6 weeks post PC-3 CaP cell inoculation, and the fat signal was suppressed using a chemical shift-selective pulse. Subsequently, the MRI data were imported into the image processing software Avizo Standard and stacked into three-dimensional (3D) volumes. Our results demonstrate that MRI, combined with 3D reconstruction, is a feasible and sensitive method to assess tumor growth in a PC-3 orthotopic CaP mouse model and this established monitoring approach is promising for longitudinal observation of CaP xenograft development after anticancer therapy in vivo . Further investigation is needed to validate this protocol in a larger cohort of mice to generate enough statistical power.